The «Rank-Size» Model As A Tool To Assess And Forecast Sustainable Development Of The System Of Cities In A Region - D. Mironova, Margarita (2019)
The article deals with the most serious problems of formation and development of the system of cities in the territory of the Russian Federation. The analysis of dynamic changes of city systems using the law "rank-size"is carried out. The author comes to the conclusion that the specific failure of the policy of urban alignment in formulating strategies for economic development of regions in the second half of the twentieth century indicates the need for large-scale approaches to solving the problem of balanced growth of urban systems that ensure sustainable economic development of regions and the country as a whole.